The clinical characteristics and risk factors of steroid-induced ocular hypertension following pars plana vitrectomy - Shuanghong Jiang; Hongxia Yang; Ting Chen; Zhenyu Ji; Xixi Yan (PLoS ONE, 2026)
Objective This study aimed to assess the incidence and risk factors for the development of steroid-induced ocular hypertension (SIOH) following 23-gauge (23G) pars plana vitrectomy. Methods The clinical data of patients treated with 23G vitrectomy from January 2019 to March 2022 were reviewed retrospectively. The incidence and characteristics of SIOH post-operatively and treatment provided were recorded. The clinical risk factors for developing SIOH were analyzed using logistic regression analysis. Results Among the 540 eligible patients, 111 (20.56%) cases developed SIOH. The majority (83.78%) of the SIOH cases developed between the third and seventh day postoperatively. Among these cases, 65 (58.56%) patients had an intraoperative pressure (IOP) of 30 mmHg or higher, and 31 (27.9%) had an IOP of 40 mmHg or higher. The IOP of all SIOH patients returned to normal within 1 month following the discontinuation of steroid and IOP-lowering medicine treatment. The independent risk factors for SIOH (IOP ≥ 23 mmHg) were myopia (odds ratio (OR) 5.22) and silicone oil filling (OR 8.20). For severe SIOH (IOP ≥ 30 mmHg) myopia and silicone oil filling were also identified as risk factors with an OR of 3.23 and 12.86, respectively. After adjusting the steroid administration pattern, the incidence of all SIOH and severe SIOH decreased to 17.11% and 9.14%, respectively. Conclusions Myopia and silicone oil filling were identified as potential independent risk factors for the development of SIOH after vitrectomy. A shorter topical steroid therapy was associated with a lower incidence of SIOH particularly in high-risk patients.